MULTICULTURAL BASED LEARNING IN INCREASING STUDENTS’ TOLERANCE ATTITUDE - Munawwir Hadiwijaya; Adi (Journey: Journal of English Language and Pedagogy, 2018)
The aim of the study is to reveal how multicultural based learning can increase the multicultural students'level of tolerance. The research is qualitative descriptive which the source of data is obtained fromobservation of the implementation of multicultural based learning in Speaking II class as well asinterviews of students and lecturer. The result shows that the students' level of tolerance increasessignificantly after the implementation. there are four indicators which supports this claim; first based onthe result of racial bias test taken by the students before and after the implementation, which the resultshows significant improvement of score,; second, based on observations on every meeting focusing onfour skills that become the emphasize of the study. Those skills are: multiculturalism skill, diversity skill,pluralism skill, and relativism skill. The students’ four skills are increased after the implementation of themodel.